Detection of VOCs and Biogenic Amines Through Luminescent Zn–Salen Complex-Tethered Pyrenyl Arms - Roberta Puglisi; Caterina Testa; Sara Scuderi; Valentina Greco; Giuseppe Trusso Sfrazzetto; Manuel Petroselli; Andrea Pappalardo (Molecules)
Amines are produced through various industrial and biological processes, contributing significantly to atmospheric pollution, particularly in the troposphere. Moreover, amine-related pollution raises global concerns due to its detrimental effects on human health, environmental quality, and the preservation of animal species. Low-molecular-weight volatile amines, categorized as volatile organic compounds (VOCs), are present in the atmosphere, and they represent the main cause of air pollution. Biogenic amines, resulting from the natural decarboxylation of amino acids, are released into the environment from both natural and industrial sources. Several methods have been developed so far to detect amines in the environment. In this study, we present a novel fluorescent receptor based on a Zn–Salen complex, functionalized with pyrenyl moieties and a chiral diamine bridge, to enhance its affinity for a broad range of amines. Fluorescence titrations and density functional theory (DFT) calculations reveal and explain the high binding affinity of this receptor toward selected amines, demonstrating its potential as an effective tool for amine detection.